2006
DOI: 10.1124/jpet.106.108092
|View full text |Cite
|
Sign up to set email alerts
|

A Polyclonal Antibody to the Prepore Loop of Transient Receptor Potential Vanilloid Type 1 Blocks Channel Activation

Abstract: Transient receptor potential vanilloid type 1 (TRPV1) can be activated by multiple chemical and physical stimuli such as capsaicin, anandamide, protons, and heat. Capsaicin interacts with the binding pocket constituted by transmembrane regions 3 and 4, whereas protons act through residues in the prepore loop of TRPV1. Here, we report on characterization of polyclonal and monoclonal antibodies to the prepore loop of TRPV1. A rabbit anti-rat TRPV1 polyclonal antibody (Ab-156H) acted as a full antagonist of proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
33
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
(32 reference statements)
1
33
1
Order By: Relevance
“…We and several others have shown that polyclonal (Zhou et al, 1998;Klionsky et al, 2006;Naylor et al, 2008) and monoclonal (Gómez-Varela et al, 2007;this study) antibodies to the third extracellular loop (loop 3) that forms the pore in different ion channels can act as antagonists (see reviews by Naylor and Beech, 2009;Sun and Li, 2013). Interestingly, most of the antibodies blocked their respective channel's activation by multiple ligands, which bind to different locations in the channel (e.g., capsaicin at transmembrane regions 2-4 and protons that act through loop 3 in TRPV1; Klionsky et al, 2006), suggesting that high-affinity binding of antibodies to the pore loop holds the channel in a closed confirmation or blocks the pore.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We and several others have shown that polyclonal (Zhou et al, 1998;Klionsky et al, 2006;Naylor et al, 2008) and monoclonal (Gómez-Varela et al, 2007;this study) antibodies to the third extracellular loop (loop 3) that forms the pore in different ion channels can act as antagonists (see reviews by Naylor and Beech, 2009;Sun and Li, 2013). Interestingly, most of the antibodies blocked their respective channel's activation by multiple ligands, which bind to different locations in the channel (e.g., capsaicin at transmembrane regions 2-4 and protons that act through loop 3 in TRPV1; Klionsky et al, 2006), suggesting that high-affinity binding of antibodies to the pore loop holds the channel in a closed confirmation or blocks the pore.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, most of the antibodies blocked their respective channel's activation by multiple ligands, which bind to different locations in the channel (e.g., capsaicin at transmembrane regions 2-4 and protons that act through loop 3 in TRPV1; Klionsky et al, 2006), suggesting that high-affinity binding of antibodies to the pore loop holds the channel in a closed confirmation or blocks the pore. Although we do not know exactly where 2B10 and 2D1 bind to the TRPA1 channels, we propose that these mAbs perhaps act through high-affinity binding to the pore loop region, based on their ability to block diverse modes of activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A glutamic residue (E600) on the extracellular side of the fifth transmembrane segment is crucial for the low pH potentiation (Jordt et al, 2000). An antibody to the region inhibits the low pH activity of the channel (Klionsky et al, 2006). Another acidic residue, E648, located in the linker between the selectivity filter and the sixth transmembrane domain, was proposed to mediate the direct response to low pH (Jordt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, antagonist binding to sites other than the capsaicin site may not modulate polymodal receptor activation induced by stimuli other than capsaicin. 42 Ruthenium red is an unspecific TRP channel blocker also antagonizing capsaicin activation of TRPV1 channels. Unlike capsazepine, AMG 9810, SB 705498 or BCTC, ruthenium red blocks the pore of the TRPV1 channel.…”
mentioning
confidence: 99%